Good Governance, Tourism Seasonality, Financial Performance, and Tax Compliance in Magelang Regency - Sunaningsih, Suci Nasehati; Nugraheni, Agustina Prativi; Khabibah, Nibras Anny; Sitoresmi, Mumpuni Wahyudiarti; Simamora, Alex Johanes (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This research examines the moderating effect of good governance (transparency, trust, ethics) on the effect of tourism seasonality-based financial performance on hotels and accommodations in Magelang Regency tax compliance. The sample includes 73 hotels and accommodations in Magelang Regency. This study measures five key variables of tourism seasonality-based financial performance, tax compliance behaviour, tax officer transparency, taxpayer trust in tax officers, and taxpayer ethics by questionnaires. Data analysis uses Structural Equation Modelling. Based on data analysis, transparency, trust, and ethics moderate the effect of tourism seasonality-based financial performance on tax compliance. The result indicates that good governance promotes transparency, trust, and ethics in profitable hotels and accommodations, which use their strong financial performance to pay and comply with taxes. This research provides evidence of seasonality-based financial performance, good governance, and tax compliance in hotels and accommodations.